Peningkatan Kualitas Jerami Padi dan Pengaruhnya Terhadap Kecernaan Nutrien dan Produk Fermentasi Rumen Kerbau dengan Feces Sebagai Sumber Inokulum - Syapura Syapura; Muhamad Bata; Wardhana Surya Pratama (Jurnal Agripet, 2013)
Improving of rice straw quality and its effect on ability nutrient digestibility and rumenmetabolism products of buffalo in-vitro with feces as inoculum sourceABSTRACT. This study was aimed to determine the effect of feeding ammoniated rice straw plus concentrate on buffalo nutrient digestibility and rumen fermentation products by in vitro.The Research was carried out by using experimental method, designed according to completely randomized design (CRD).The source of inoculum was obtain from different feces of three buffalos kept in Datar Village of Purwokerto region fed rice straw, rice straw plus concentrate and rice straw ammoniated plus concentrate with dry matter ratio of 80 : 20.The treatments tested consisted of three treatments, namely R0 = control feed using rice straw; R1 = the use of rice straw plus concentrate with a ratio of (DM basis) 80:20; R2 = the use of ammoniated rice straw plus concentrate with a ratio of (DM basis) 80:20. The treatments were repeated 7 times, so there were 21 experimental units.The Variables measured included total VFA, Ratio A/P, N-NH3, Microbial Protein Synthesis (MPS), Dry Matter and Organic Matter Digestibility. The result of this study showed that the treatment had an effect significant (P0.05) on the concentration of VFA, Ratio A/P, N-NH3, Microbial Protein Synthesis (MPS), and Dry Matter and Organic Matter Digestibility. The HSD test showed that the highest production of VFA,Ratio A/P, N-NH3, Microbial Protein Synthesis (MPS), Dry Matter and Organic Matter Digestibility were achieved at R2 followed by R1 and R0 respectively. The conclusion is that the ammoniated rice straw supplemented with concentrate can be recommended to be fed to buffalo